Distinct Age-Specific Effects on Olfactory Associative Learning in C57BL/6 Substrains - Chen, Hung-Lun; Chen, Chien-Fu F.; Huang, Han-Bin (Frontiers in Behavioral Neuroscience, 2022)
C57BL/6 is the most widely used mouse strain in the laboratories. Two substrains of C57BL/6, C57BL/6J (B6J) and C57BL/6N (B6N) are well-known backgrounds for genetic modification and have been shown different in quite a few tests, including open field test, rotarod test and Morris water maze. However, difference between these two substrains in olfaction-dependent behaviors remains unknown. Here, we used olfactory two-alternative choice task, which is modified to have two training stages, to evaluate animals’ ability in instrumental learning and olfactory association. In the first (rule learning) stage, the mice were trained to use the operant chamber to collect water rewards. An odor cue was provided in the procedure, with no indication about reward locations. In the following (discrimination learning) stage, two odor cues were provided, with each indicating a specific water port. The animals were rewarded upon correct port choices following cue deliveries. We found that during young adulthood (7 to 10 weeks old), proportionally more B6J than B6N mice were able to pass rule learning stage (58.3% vs. 29.2%) and ultimately acquire this task (54.2% vs. 25%), with their pass rates similar in discrimination learning stage. Surprisingly, at a more mature age (17 weeks old), this substrain difference disappeared. Mature B6N mice had a significant improvement in pass percentages of rule learning stage and overall task, while similar improvement was not observed in mature B6J mice. Instead, mature B6J mice had an improved speed in rule learning stage and overall task. We further test young adults of these two substrains with olfactory habituation/dishabituation paradigm. We found that the B6J mice exhibited stronger investigative responses to cotton swabs scented with new odors. These results reveal for the first time that B6J and B6N mice are different in acquisition processes of a behavior that requires instrumental learning and olfactory association, and that maturation appears to employ different effects on these two substrains during these processes. Furthermore, the observation that the B6J and B6N mice respond differently to novel scented objects in the environment suggest a potential difference of these two mice substrains in olfactory aspect of novelty seeking.